2005
DOI: 10.1111/j.1439-054x.2005.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders and Behavioural Problems among 8- to 11-Year-Old Children. Schlafstorungen und Verhaltensprobleme bei 8-11 Jahre alten Kindern

Abstract: Question of the study To assess the prevalence of sleep disorders in 8-to 11-year-old children and their relation to behavioural problems. Study design A population based, cross-sectional survey was carried out among fourthgrade elementary school children in Cologne, Germany. A total of 8599 children were enrolled. Parent-completed and children-completed questionnaires were used to ascertain sleep disorders and behavioural problems. Results In all, 4531 questionnaires were completed. Parent-reported sleep onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…For children, socioeconomic status is associated with sleep and insomnia duration ( 40 ). Living conditions in less developed urban areas, with poor hygiene, poverty, and low income, can lead to sleep disorders ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…For children, socioeconomic status is associated with sleep and insomnia duration ( 40 ). Living conditions in less developed urban areas, with poor hygiene, poverty, and low income, can lead to sleep disorders ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep problems are frequent in children and adolescents [1,2,3,4,5,6,7,8,9]. Kahn et al [6] surveyed 1,000 (972 were completed and could be used for statistical analysis) elementary school children from the third, fourth, and fifth grades and discovered that sleep difficulties lasting more than a few months were present in 43% of the children.…”
Section: Introductionmentioning
confidence: 99%
“…The Japanese version of the BCSQ has been con rmed for reliability and validity. 26 Three-way frequency assessments (1: rare [1 day/week or less]; 2: occasionally [2-4 days/week]; 3: almost always [5-7 days/week]) were used to evaluate four symptoms at bedtime ( [1] child falls asleep with rocking or rhythmic movements, [2] child needs special object to fall asleep [doll, special blanket, etc. ], [3] child resists going to bed at bedtime, and [4] child is afraid of sleeping in the dark), nine symptoms during sleep ( [5] child talks during sleep, [6] child is restless and moves a lot during sleep, [7] child sleepwalks during the night, [8] child grinds teeth during sleep, [9] child snores loudly, [10] child seems to stop breathing during sleep, [11] child snorts and/or gasps during sleep, [12] child awakens during the night screaming, sweating, and inconsolable, [13] child awakens alarmed by a frightening dream), ve symptoms at wake time ( [14] child wakes up in a negative mood, [15] child has di culty getting out of bed in the morning, [16] child takes a long time to become alert in the morning, [17] child wakes up very early in the morning, [18] child has a good appetite in the morning), and one symptom during the day ( [19] child suddenly falls asleep in the middle of active behavior) (see Table S1).…”
Section: Brief Child Sleep Questionnairementioning
confidence: 99%
“…Sleep plays an important role in child development. In addition to being associated with childhood body growth, 1 behavior, 2 and emotion, 3 sleep is also closely related to cognitive function, 4 school behavioral assessment, 5,6 and cautioning by teachers about behavior. 7 A recent systematic review of sleep habits (i.e., sleep onset time, wake time, and total sleep time [TST]) of children aged 0 to 12 years reported that children aged 6 to 12 years have an average sleep time of 9 hours and 12 minutes, with the sleep time of children in Asian countries, including Japan, approximately 1 hour shorter than that of children in other countries.…”
Section: Introductionmentioning
confidence: 99%